Scaffolding with Peer Tutoring in the Teacher's Perspective: Could Its Implementation in Learning Programs Improve Scientific Communication Skills and HOTS - Duwita Pangesti Putri; Tri Jalmo; Agus Suyatna (Postgraduate, University of Mataram, 2023)
This essay's purpose is to provide a summary the perceptions of science teachers towards scaffolding learning programs with peer tutoring in improving scientific communication skills and HOTS. This research was conducted in the province of Lampung, Indonesia, involving 74 middle school science teacher respondents. A mixed method with a sequential explanatory design was used for the study. Data were collected through interviews and surveys, and descriptive analysis was used to analyse the results. The survey findings indicate that science instructors have a favourable opinion of using scaffolding in conjunction with peer tutoring. The analysis's findings indicate that most instructors have not used peer tutoring and scaffolding in the classroom to help students advance from their current competencies to potential competencies. In addition, teachers also have not implemented scaffolding learning programs with peer tutoring.